TO THE STUDY OF THE PROCESSES OF CHARGING AND DISCHARGING A CAPACITOR - Israilov М. (Web of Journals Publishing, 2024)
This article is devoted to the theory of the processes of charging and discharging capacitors, using it as laboratory work, you can experimentally determine the capacitance of the capacitor.
Keywords: charge, discharge, quasi-stationary current, differential equation, asymptotics, exponential law, RC circuit, initial state.